Pengaruh Metode Demonstrasi Berbantuanmedia Vidio terhadap Hasil Belajar Pemangkasan Rambut Solid pada Mahasiswa Aks Ibu Kartini Semarang - Aulia Romadona; Kuswidyaningrum N. J. (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2026)
The purpose of this study was to determine the learning outcomes of second-semester students in solid hair trimming skills after receiving learning through compression methods using video-based media or compression methods without media, also to analyze how influential video media in compression methods are on student learning outcomes on trimming material. The following study is a type of quasi-experimental research. With the results showing that the average post-test score of experimental class students, who were given learning using the exposure method with the help of video media on solid hair trimming material, was 83.93. On the other hand, the control class, which was given demonstration learning without video media. The average post-test score was 79.30. The results of the Hypothesis test showed a calculated value greater than the t table (4.158 > 2.00) and a significance value of 0.0000 smaller than 0.05. Therefore, it can be concluded that explanations with the help of video media have an influence on learning outcomes in solid hair trimming in second-semester students. In addition, this method has an effect of increasing by 5.84% on learning outcomes compared to the demonstration method without media.Keywords: Demonstration Method, Video, Solid Hair Cutting